Going Mobile: Resident Physicians' Assessment of the Impact of Tablet Computers on Clinical Tasks, Job Satisfaction, and Quality of Care - Sweeney, Megan; Paruchuri, Kaavya; Weingart, Saul N. (Applied Clinical Informatics, 2018)
Background There are few published studies of the use of portable or handheld computers in health care, but these devices have the potential to transform multiple aspects of clinical teaching and practice.Objective This article assesses resident physicians' perceptions and experiences with tablet computers before and after the introduction of these devices.Methods We surveyed 49 resident physicians from 8 neurology, surgery, and internal medicine clinical services before and after the introduction of tablet computers at a 415-bed Boston teaching hospital. The surveys queried respondents about their assessment of tablet computers, including the perceived impact of tablets on clinical tasks, job satisfaction, time spent at work, and quality of patient care.Results Respondents reported that it was easier (73%) and faster (70%) to use a tablet computer than to search for an available desktop. Tablets were useful for reviewing data, writing notes, and entering orders. Respondents indicated that tablet computers increased their job satisfaction (84%), reduced the amount of time spent in the hospital (51%), and improved the quality of care (65%).Conclusion The introduction of tablet computers enhanced resident physicians' perceptions of efficiency, effectiveness, and job satisfaction. Investments in this technology are warranted.
Keywords: tablet computers; interns and residents; information technology; health care informatics